Benzoic Acid and Sorbic Acid Levels in Some Dairy Products Consumed in Turkey - KOYUNCU, NIHAN; UYLASER, VILDAN (Asian Journal of Chemistry, 2010)
In this study, white cheese, kashar cheese, yogurt, ayran, mayonnaise and margarine samples of different brands were analyzed for benzoic and sorbic acid levels. They were obtained from retail outlets in Bursa, Turkey. The occurrence and concentration level of benzoic acid and sorbic acid in the samples were investigated using high performance liquid chromatography (HPLC) with diode-array detector (235-254 nm). Chromatographic separation was achieved with a C18 column and acetate buffer (pH 4.74)-methanol mixture (70:30) as a mobile phase. The levels of benzoic acid and sorbic acid in the analyzed samples were in the range of not detected to 466 mg/kg or L and 2.09 to 1133 mg/kg or L, respectively. In 80 and 40 % of the analyzed yogurt samples, 100 and 20 % of the analyzed ayran samples, 80 % of the analyzed white and kashar cheese samples established benzoic acid and sorbic acid, respectively, although not permitted by the Turkish Food Codex. Benzoic acid and sorbic acid levels in the other samples were determined in the maximum tolerable limit of the Turkish Food Codex.